Boards’ Characteristics, Voluntary Disclosure, and Accounting Information Value Relevance – Indonesian Evidence - Krismiaji, Krismiaji; Kusumadewi, Hermala (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2019)
This paper describes empirical evidence which investigates the effect of boards’ characteristics and voluntary disclosure on the accounting information value relevance. Voluntary disclosure (VD) is measured by voluntary disclosure index, a measure which in line with some regulations in Indonesia, especially the Company Act No. 40 of 2007 about the limited corporation; board’s characteristics are proxy by board’s independence (BIN) and board’s size (BSIZE), whereas value relevance is measured by the Ohlson Price Model. Using the 119 manufacturing firms listed in the Indonesian Stock Exchange (IDX) for the year of 2011 to 2015 as a sample, taken by purposive sampling technique, this study finds that the voluntary disclosure strengthens the value relevance of earnings number but decreases the value relevance of book value number. Moreover, board size strengthens the value relevance of earnings and book value. Finally, board independence strengthens the value relevance of earnings number and book value number. This study provides additional evidence about the influence of boards’ characteristics and the effect of voluntary disclosure on the value relevance of accounting information with the evidence from Indonesia. Paper ini menguraikan hasil penelitian yang menginvestigasi pengaruh pengungkapan karakteristik dewan komisaris dan pengungkapan sukarela terhadap relevansi nilai informasi akuntansi. Pengungkapan sukarela (VD) diukur menggunkaan indeks pengungkapan, sesuai dengan regulasi yang berlaku di Indonesia, khususnya Undang- undang Perseroan Terbatas No. 40 tahun 2007 tentang perseroan terbatas; karakteristik dewan komisaris diproksi dengan independensi (BIN) dan ukuran (BSIZE), sedangkan relevansi nilai diukur dengan Model Harga Ohlson. Dengan menggunakan data perusahaan manufaktur yang terdaftar di Bursa Efek Ilndonesia (IDX) pada tahun 2011 sampai 2017 yang dipilih menggunakan teknik purposive sampling, penelitian ini menemukan bahwa pengungkapan sukarela memperkuat relevansi nilai laba namun menurunkan relevansi nilai untuk nilai buku. Selain itu, ukuran dewan komisaris memperkuat relevansi nilai laba dan nilai buku. Terakhir, independensi dewan komisaris juga memperkuat relevansi nilai laba dan nilai buku. Hasil penelitian ini melengkapi hasil penelitian sebelumnya tentang pengaruh karakteristik dewan komisaris dan pengungkapan sukarela terhadap relevansi nilai informasi dengan menggunakan data perusahaan di Indonesia.